2001
DOI: 10.4049/jimmunol.166.4.2270
|View full text |Cite
|
Sign up to set email alerts
|

Effector Function of Resting T Cells: Activation of Synovial Fibroblasts

Abstract: Synovial tissue in rheumatoid arthritis is characterized by infiltration with large numbers of T lymphocytes and APCs as well as hyperplasia of synovial fibroblasts. Current understanding of the pathogenesis of RA includes the concept that synovial fibroblasts, which are essential to cartilage and bone destruction, are regulated by cytokines derived primarily from monocyte-macrophage cells. Recently it has been found that synovial fibroblasts can also function as accessory cells for T cell activation by supera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 18 publications
2
69
2
Order By: Relevance
“…We found that the production of IL-8, MCP-1, and MIP-1␣ was significantly augmented when FLS were cocultured with CIIstimulated T cells. Recently, Yamamura et al demonstrated that resting T cells, even in the absence of T cell mitogens or antigens, could induce activation of FLS when cocultured (36). In the present study, although the production of chemokines from FLS was slightly increased by interaction with resting T cells, it was augmented much more by interaction with CII-stimulated T cells.…”
Section: Discussioncontrasting
confidence: 51%
“…We found that the production of IL-8, MCP-1, and MIP-1␣ was significantly augmented when FLS were cocultured with CIIstimulated T cells. Recently, Yamamura et al demonstrated that resting T cells, even in the absence of T cell mitogens or antigens, could induce activation of FLS when cocultured (36). In the present study, although the production of chemokines from FLS was slightly increased by interaction with resting T cells, it was augmented much more by interaction with CII-stimulated T cells.…”
Section: Discussioncontrasting
confidence: 51%
“…Using resting T cells as a stimulus, we have documented activation of FLS and release of proinflammatory mediators [13]. We found that autologous or allogeneic resting T cells have similar activating potential on FLS.…”
Section: Synovial Fibroblast Activation By T Cellsmentioning
confidence: 87%
“…PGE 2 , which can be produced by fibroblasts, was shown to have anti-proliferative effects on T lymphocytes and to decrease IFN-γ levels, but more recent evidence has shown that PGE 2 augments T H 17 cell differentiation [119] and this may serve as another pathway by which fibroblasts could contribute to inflammatory disorders. Conversely, IL-17A has been shown to cause an increase in fibroblast PGE 2 production [120].…”
Section: Fibroblast Products As Promoters Of Inflammationmentioning
confidence: 99%